Research in the Social Scientific Study of Religion. - Piedmont, Ralph L.; Village, Andrew. (Research in the Social Scientific Study of Religion, 2012)
The social scientific study of religion is a crucial arena of human endeavor, as questions about the existence and nature of God interact with the study of religion as a human phenomenon. The twenty-third volume of RSSSR continues the tradition of promoting extended debate of current issues in the field. The special section on Theism and Non-Theism in Psychological Science includes contributions from leading researchers in this area. This landmark collection of papers draws on a range of perspectives that both summarize the theism debate in psychology and help to move it forward in new directions. In addition, the volume includes papers on other key areas in the study of religion such as spirituality and social capital.